The Position of Election Law in Ensuring Regional Political Justice and Stability - Pradipta, Arga Mahawira (Penerbit Mandalika Indonesia, 2025)
Elections are a fundamental pillar of democracy, ensuring fair political representation and stability at both national and regional levels. However, challenges such as electoral fraud, weak law enforcement, and political interference continue to undermine electoral justice, particularly in decentralized governance structures. This study examines the position of election law in ensuring regional political justice and stability by analyzing Indonesia's legal framework, institutional mechanisms, and electoral dispute resolution processes. Using a qualitative research method with a literature study approach (library research), this study reviews constitutional provisions, electoral laws, and previous scholarly findings to assess the effectiveness of election regulations in preventing fraud, ensuring fairness, and maintaining democratic stability. The findings highlight that while Indonesia has a strong legal foundation for elections, weaknesses persist in law enforcement, electoral dispute resolution, and the independence of election management bodies. The role of Komisi Pemilihan Umum (KPU), Badan Pengawas Pemilu (Bawaslu), and Dewan Kehormatan Penyelenggara Pemilu (DKPP) remains crucial in maintaining electoral integrity, yet political interference and resource constraints often limit their effectiveness. Additionally, unresolved electoral disputes contribute to political tensions, governance deadlock, and loss of public trust in democracy. The study concludes that strengthening electoral law enforcement, enhancing institutional independence, and updating regulations for digital election practices are essential steps toward improving electoral justice and stability. Future research should explore comparative legal analyses, digital election security, and the effectiveness of legal sanctions in reducing electoral fraud. By addressing these issues, electoral governance can be improved to sustain regional democratic stability and public confidence in electoral systems.